Information systems - Stair, Ralph M.; Reynolds, George Walter, 1944- (Australia : Course Technology/Cengage Learning, 2010)
Covers IS principles and their real-world applications using business examples and activities. This book helps students understand and practice IS principles to function effectively as workers, managers, decision makers, and organizational leaders.
PART 1: AN OVERVIEW: An introduction to information systems -- Information systems in organizations -- PART 2: INFORMATION TECHNOLOGY CONCEPTS: Hardware: input, processing, and output devices -- Software: systems and application software -- Database systems and business intelligence -- Telecommunications and networks -- The Internet, intranets, and extranets -- PART 3: BUSINESS INFORMATION SYSTEMS: Electronic and mobile commerce -- Enterprise systems -- Information and decision support systems -- Knowledge management and specialized information systems -- PART 4: SYSTEMS DEVELOPMENT: Systems development: investigation and analysis -- Systems development: design, implementation, maintenance, and review -- PART 5: INFORMATION SYSTEMS IN BUSINESS AND SOCIETY: The personal and social impact of computers -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: Management information systems